(untitled) (Journal of the College of Basic Education, 2022)
Human societies try to provide their generations with the best types of education through the processes of education. Therefore, it has become necessary to reconsider the educational curricula, its objectives, and teaching methods and methods to keep pace with Social, economic and scientific changes (Haggai 19). For this reason, problems arise in the teaching of any new subject in learning that subject. The history of the Kurds, which is taught to the third-year students of the history department, as the matter becomes more difficult and complicated when This course is taught to students who do not have any background in their studies of previous years.